ARTISTIC ANTROPOLOGY IN THE SHORT STORIES OF MARKO CHEREMSHYNA - Liakh, T. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The characteristic features of the Ukrainian literary process at the end of XIXth – the beginning of XXth centuries develop in connection with Modernism. Ukrainian writers reflected the realities of human life and psychological states, feelings of the characters. Marko Cheremshyna’s worldview was formed in the cultural context and philosophy of his time. Writer’s works are closely connected to Modernism tendencies especially to the transcendental sphere that forms the metaphysical horizon of the author’s fiction. The relevance of the research is determined by the fact that there is a need to study the writer’s artistic anthropology in connection with his own philosophical understanding of human existence in the world. Therefore, the article deals with Marko Cheremshyna’s artistic anthropology and metaphysic sphere of human and the world. Aesthetic, psychoanalytic, and hermeneutic methods were used in the research. In this study it was found that the metaphysical horizon of man and the world is primarily manifested by Marko Cheremshyna through the existential states, when the person opens the “supersensual”, “divine being” and is closely connected to the transcendental sphere. Such an approach of the writer to the creation of artistic anthropology was facilitated both by the modernist reception of folklore and mythological images and motifs, and by the latest directions of European philosophy, in particular the philosophy of F. Nietzsche. The investigation also focuses on the vitality motif in Marko Cheremshyna’s short stories of the cycle “Parasochka”. Solving this problem is connected with questions of nature, love, essence and sense of human life. Analysis of the writer’s artistic anthropology clarifies the inexhaustible phenomenon of his work. The research complements the idea of the special philosophical type of thinking of Marko Cheremshyna, outlines further aspects of the study of his short storiesin relation to the interdisciplinary research.